SAT-118 Gastric Sleeve for Adjunctive Management of Nonalcoholic Steatohepatitis: A Case Report - Horowitz, Alex (J Endocr Soc, 2019)
Introduction: The prevalence of Nonalcoholic Steatohepatitis (NASH) has increased 2.5-fold over the last 20 years in the United States (1). NASH is currently the second most common etiology for liver transplant listings, and in women is the leading cause (2). Life-style changes to include weight loss, diet and exercise remain the core interventions to help prevent progression of NASH. Sleeve gastrectomy, an alternative to gastric bypass, results in significant weight loss and improvement in obesity-related co-morbidities such as glucose metabolism and metabolic syndrome. We present a patient who had a sleeve gastrectomy as adjunctive treatment for NASH. Case Description: A 59 year old female presented to the Gastroenterology clinic for evaluation of NASH and abnormal liver enzymes. She had elevated liver enzymes, alkaline phosphatase 173 IU/L, aspartate aminotransferase 63 IU/L, alanine aminotransferase 86 IU/L, with a normal bilirubin 0.3 mg/dL. Fasting labs were notable for a glucose of 130 mmol/L, insulin level of 72 mIU/L, and calculated Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) of 23.1. Other labs for viral, inherited and acquired etiologies for abnormal liver studies were benign. The patient subsequently had a sleeve gastrectomy and lost 60 lbs over 4 months. Her transaminases normalized and insulin dropped to 13 mIU/L with a calculated HOMA-IR of 3.1 Final/Working Diagnosis: NASH related dysmetabolic syndrome. Management/Outcome/Follow-up: The patient will continue dietary changes and exercise to emphasize a healthy lifestyle. Her gastric sleeve will help with long-term weight loss management which is key to controlling insulin resistance and prevention of further liver damage.